Should low-wage workers care about where they work? Assessing the impact of employer characteristics on low-wage mobility - Guertzgen, Nicole; Heinze, Anja (Mannheim, 2010)
"The present paper studies the importance of employer-specific determinants in escaping low earnings in Germany. In our empirical analysis, we draw particular attention to the role of employer size and the nature of industrial relations. We hypothesise employer size to have an ambiguous impact on low-wage mobility for two reasons. On the one hand, employer size is typically viewed a good proxy for the presence of internal job ladders, thereby promoting intra-firm wage mobility. On the other hand, larger employer are likely to face a higher degree of information asymmetries about workers' true productivity, which may hamper intra-firm wage growth. Industrial relations may be viewed as a potential means to overcome these informational problems as, e.g., local worker representations are actively involved in monitoring promotions and reducing information asymmetries concerning workers' productivity levels. Using data from a large-scale linked employer-employee panel data set, our findings indicate that employer characteristics play an important role in helping workers to escape their low pay status, though they point to different patterns across gender. While for male workers from the service sector the probability of escaping low pay tends to increase with employer size, female workers rather benefit from collective bargaining coverage contracts and the presence of local works councils. While these findings provide evidence that internal labour markets are an important ingredient of male within-firm wage growth, they do not necessarily contradict the view that internal labour markets may also exist for female low-wage workers. The only conclusion that can be inferred from our findings is that for females there are potential countervailing effects of plant size which might arise from a larger degree of asymmetric information. Along with the differences in the industrial relations effects this leads us to conclude that the removal of asymmetric information appears to be more relevant in explaining female workers' wage transitions as compared with their male counterparts. This finding is consistent with incomplete information about workers' true productivity being particularly relevant for individuals whose employment careers are more frequently characterised by earlier career interruptions, making it difficult to value their productivity based upon previous work performance."